2017
DOI: 10.1002/2017gl074626
|View full text |Cite
|
Sign up to set email alerts
|

Episodic inflation events at Akutan Volcano, Alaska, during 2005–2017

Abstract: Detection of weak volcano deformation helps constrain characteristics of eruption cycles. We have developed a signal detection technique, called the Targeted Projection Operator (TPO), to monitor surface deformation with Global Positioning System (GPS) data. We have applied the TPO to GPS data collected at Akutan Volcano from June 2005 to March 2017 and detected four inflation events that occurred in 2008, 2011, 2014, and 2016 with inflation rates of about 8–22 mm/yr above the background trend at a near‐source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Akutan volcano has shown multiple episodic inflation events that have occurred approximately every 2-3 years (Figure 2b). The inflation events in 2008,2011,2014, and 2016 already were identified by previous studies (DeGrandpre et al, 2017;Ji et al, 2017;Ji & Herring, 2011), and the estimated volume increase of each event is consistent with the previous results. We also find two earlier events that happened in 2004 and 2006, when only the AVO continuous GPS sites were operational, and an inflation event that has been ongoing since 2019.…”
Section: Resultssupporting
confidence: 91%
“…Akutan volcano has shown multiple episodic inflation events that have occurred approximately every 2-3 years (Figure 2b). The inflation events in 2008,2011,2014, and 2016 already were identified by previous studies (DeGrandpre et al, 2017;Ji et al, 2017;Ji & Herring, 2011), and the estimated volume increase of each event is consistent with the previous results. We also find two earlier events that happened in 2004 and 2006, when only the AVO continuous GPS sites were operational, and an inflation event that has been ongoing since 2019.…”
Section: Resultssupporting
confidence: 91%
“…For example, before its 2010 eruption, repeated episodes of magma intrusion and accumulation were found beneath Eyjafjallajökull, Iceland (Sigmundsson et al, 2010). In the Aleutian arc, multiple episodic inflation events have been observed at Akutan volcano from 2005 to 2017 (DeGrandpre et al, 2017;Ji et al, 2017). Episodic inflation events are common at Kilauea volcano in Hawaii as well (e.g., Cervelli & Miklius, 2003); in that case, episodic deflation-inflation events were interpreted to result from short-lived blockages in the magma supply.…”
Section: Magma Supply Dynamicsmentioning
confidence: 99%
“…Real-time geophysical monitoring is a fundamental tool for tracking and understanding volcanic activity and real-time hazard assessment (e.g., Scarpa and Tilling, 1996;Sparks et al, 2012;Ji et al, 2017). In the aftermath of Iceland's Ejafyallajokull eruption of 2010 numerous working groups and think-tanks (Wotawa and Stohl, 2012;Bonadonna, 2014;Brenot et al, 2014) identified real-time tracking of particle size distribution (PSD), in synergy with plume modeling, as a fundamental need for improved hazard assessment and effective management of volcanic crises.…”
Section: Introductionmentioning
confidence: 99%